Rancang Bangun Sistem Informasi Penyedia Jasa Instalasi Listrik Berbasis Web dengan Metode OOAD : Studi Kasus pada CV Givas Jaya Sentosa - Agung Tri Laksono Aji Saputra; Laila Khusnul Afifah; Dinda Ana Pratiwi (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2026)
The development of information technology requires service companies to improve the effectiveness and quality of their services, including in the field of electrical installation services. CV Givas Jaya Sentosa still faces problems in managing orders, customer data, and technician scheduling, which are done manually, resulting in inefficiency. This study aims to design and build a web-based electrical installation service provider information system using the Object Oriented Analysis and Design (OOAD) method. The research method used is qualitative with a research and development (R&D) approach, through data collection techniques such as observation, interviews, and documentation. The system is designed using Unified Modeling Language (UML) modeling and implemented as a web application. The results of the study show that the system is able to simplify the service ordering process, improve service and technician data management, and help monitor work status in an integrated and real-time manner. Thus, this information system can improve operational efficiency and service quality at CV Givas Jaya Sentosa.